2006
DOI: 10.1375/jhtm.13.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Major Factors Influencing Consumer Selection of Travel Agencies in a Regional Setting

Abstract: Exploring the major factors influencing consumer selection of travel agencies in a regional setting AbstractThe research reported in this paper explores why consumers choose to book their travel arrangements with travel agencies in regional settings. Consumers can now access on-line bookings for airlines, accommodation, transportation, sightseeing tours and other related products so why do they still go to travel agencies for reservations? This paper identifies the attributes which consumers seek in a travel a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The following statement sums up this sentiment: "It will be years, if ever, before computers give us anything close to the warm and personal service we hope to get from dealing with a live travel agent" (Needle 1998, cited in Lang 2000. The literature on the topic abounds with similar conclusions (e.g., Bloch and Segev 1996;alba, Lynch, and Weitz 1997;Passmann, Pipperger, and Schertler 1997;Lang 2000;Lord Marshall 2000;Laws 2001;Ng, Cassidy, and Brown 2006).…”
Section: Literature Reviewmentioning
confidence: 83%
See 2 more Smart Citations
“…The following statement sums up this sentiment: "It will be years, if ever, before computers give us anything close to the warm and personal service we hope to get from dealing with a live travel agent" (Needle 1998, cited in Lang 2000. The literature on the topic abounds with similar conclusions (e.g., Bloch and Segev 1996;alba, Lynch, and Weitz 1997;Passmann, Pipperger, and Schertler 1997;Lang 2000;Lord Marshall 2000;Laws 2001;Ng, Cassidy, and Brown 2006).…”
Section: Literature Reviewmentioning
confidence: 83%
“…The aim is to identify which factors can best predict whether a traveler will seek information in person from a travel agent or directly from a tourism service provider T he proliferation of the Internet has vastly improved the direct communication between travelers and tourism service providers and thus challenged the very raison d'être of many intermediaries in the tourism distribution chain (Christou and Kassianidis 2002). The issue of disintermediation has been characterized by some authors as one of the biggest single issues facing the tourism industry (Inkpen 1998), and scholars have emphasized the need for further research into the factors that influence consumers' choice between traditional travel agencies and their online alternatives (Ng, Cassidy, and Brown 2006;Cheyne, Downes, and Legg 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A study in an Australian setting found that the most influential factors in agency selection are closely related to travel professionals, including their knowledge and experience as well as their helpfulness and friendliness (Ng, Cassidy, & Brown, 2006). One from Singapore reported that the most important factor is value for money, followed by agency reputation (Hui & Wan, 2006).…”
Section: The Literature Themes Derived From Journal Articlesmentioning
confidence: 99%
“…Nevertheless, travel agencies have been regarded as critical information and planning or booking providers for a large number of travellers (Buhalis, 1998;Buhalis & Deimezi, 2003;Duke & Persia, 1993;Mihalik, Uysal & Pan, 1995). Other studies have also investigated several different aspects of travel agencies, such as information technology needs (Bennett, 1993;Buhalis, 1998;Buhalis & Deimezi, 2003), travel agent's role in family decision-making (Wang, Hsieh, Yeh & Tsai, 2004), advertising strategies (Laskey, Seaton & Nicholls, 1994), the more effective use of relationship marketing (Bennett, 1993;Richter, 1996) and the selection attributes of travel agencies (Buhalis, 1998;Meidan, 1979;Ng, Cassidy & Brown, 2006;Oppermann, 1998;Persia & Gitelson, 1993).…”
Section: Literature Reviewmentioning
confidence: 99%